Faktor-Faktor yang Berhubungan dengan Pelaksanaan Kelas Ibu Hamil di Klinik Serasi Medika Kabupaten Banyuasin - Nova Kristiani Sipayung; Hasbiah Hasbiah; Erma Puspitasari (Universitas Batanghari Jambi, 2022)
The class for pregnant women is a community empowerment activity through group learning facilities about the health of pregnant women by using the MCH handbook. The class of pregnant women will have an influence on pregnant women in the process of preparing for childbirth. Because taking classes for pregnant women can increase knowledge, skills and motivation related to awareness to improve the health status of mothers and babies. This results in the mental readiness factor of pregnant women in facing childbirth. The purpose of this study was to determine the relationship between knowledge, motivation, husband's support and support from health workers with the implementation of classes for pregnant women at Serasi Medika Clinic, Banyuasin Regency. The research design uses an Analytical Survey with a Cross Sectional approach. The population in this study were all 32 pregnant women at Serasi Medika Clinic. The sampling technique in this study was carried out by a total sampling of 32 respondents. Collecting data using a questionnaire sheet. Data analysis using univariate analysis and bivariate analysis using chi square test. The results of this study showed that there was a relationship between knowledge (p value = 0.008), motivation (p value = 0.013), and husband's support (p value = 0.019) with the implementation of the class for pregnant women. However, there was no relationship between the support of health workers (p value = 0.380) with the implementation of the class for pregnant women. The conclusion of this study is that there is a relationship between knowledge, motivation and husband's support with the implementation of the pregnant women class, but there is no relationship between the support of health workers and the implementation of the class for pregnant women.